An intelligent and multi-terrain navigational environment monitoring robotic platform with wireless sensor network and internet of robotic things. (3rd July 2020) - Singh, Rajesh; Gehlot, Anita; Samkaria, Rohit; Choudhury, S.
Wireless sensors network (WSN) and internet of robotic things (WSN&IRT) have been emerged as fundamental data-gathering tools for the deployment of an environment monitoring system. The challenging issue in the environment monitoring system is the critical design of system architecture, coverage of monitoring area, energy efficiency of sensors and validity of the data. In this paper, design and implementation of an intelligent and multi-terrain navigational environment monitoring system with WSN&IRT is discussed. It measures and analyze the air quality, whether it is breathable by human or not. The robot measures four chemical and four physical parameters, dust particle size and communicates it to server in real-time with autonomous navigation. Artificial vision system, by using a camera is placed in the robot head for image capturing which is processed at server. The energy efficient reporting mechanism is implemented to prevent the redundant transmission of sensor data and equipped with a docking station to charge it.